Turnover in male dominance offsets the positive effect of polygyny on within-group relatedness. (6th February 2023) - Dyble, Mark; Clutton-Brock, Tim H
Abstract: Evidence of an association between cooperative breeding systems and average coefficients of relatedness between group members in vertebrates have led to increased interest in the social and ecological factors affecting average kinship within groups. Previous studies have suggested that polygynous mating systems and high degrees of male reproductive skew increase average relatedness because they increase the proportion of offspring born in each group that are paternal siblings. Although this may be the case in semelparous organisms, in many multiparous polygynous animals, intense competition between males shortens the breeding tenure of males and leads to their frequent replacement by competitors which reduces paternal relatedness and average kinship between members of multigenerational groups. Here, we explore the interaction between male reproductive skew and the frequency of turnover in breeding males and its effects on within-group relatedness. Our theoretical model shows that increases in rates of dominance turnover in polygynous systems can offset the positive effect of male skew on relatedness between group members within seasons, showing that polygynous mating systems will not necessarily lead to significant increases in average relatedness, especially in species where there is extensive overlap between generations among group members. Abstract : In species with polygynous mating systems, one male mates with several females, resulting in high male reproductive skew and the production of paternal half siblings. This might be expected to increase genetic relatedness within groups. However, reproductive skew introduces intense competition between males which often results in frequent changes in male dominance. This turnover in dominance means that genetic relatedness within multigenerational groups of polygynous animals may not necessarily be much greater than levels under monogamous mating.